Effect of fillers on the behaviour of low carbon footprint concrete at and after exposure to elevated temperatures. (1st July 2022) - Lai, M.H.; Huang, Z.C.; Wang, C.T.; Wang, Y.H.; Chen, L.J.; Ho, J.C.M.
Abstract: Low carbon footprint concrete (LCFC), which is produced by using fillers, such as ground granulated blast furnace slag (GGBFS), fly ash (FA) and silica fume (SF), etc. to replace partial cement, has become increasingly popular due to its low-cost, sustainable and superior mechanical performance. This paper establishes a systematic and scientific experimental study to investigate the effect of GGBFS, FA and SF on the behaviour of LCFC at and after exposure to elevated temperatures. The heating temperature – time curve, mass loss, surface change, spalling behaviour, failure mode and residual compressive strength of ten groups of concrete mixes with different filler types and replacement volumetric ratios were studied at and after exposure to 400, 600, 800 and 1000 °C. Test results showed that the heat-insulation capacity of LCFC was enhanced. Besides, explosive spalling was observed only for concrete containing SF with replacement ratio ≥10% at elevated temperatures ≥600 °C. The larger the ratio, the higher was the probability of spalling. To avoid this undesirable failure mode, concrete's wet packing density ≤0.8280 was recommended. Moreover, the residual compressive strength (index) improved for concrete containing OPC only, GGBFS and FA (≤25% replacement ratio) after exposure to 400 °C due to rehydration effect. After exposure to elevated temperatures ≥600 °C, the residual strength reduced significantly. For concrete containing GGBFS and FA, the residual strength (index) was larger than that of OPC concrete. Lastly, it was found that the prediction of EC2 was conservative by comparing the measured residual strength of concrete with and without fillers with that predicted by the code. Highlight: - Concrete with fillers has lower temperature rise than OPC concrete in furnace test - Concrete with slags and fly ash presented minor and finer cracks at elevated temperature - Explosive spalling was observed only for concrete with ≥10% silica fume - Maximum wet packing density of 0.8280 is proposed to avoid explosive concrete spalling